Prenatal exposure to traffic-related air pollution and risk of congenital diseases in South Korea - Lee, Kyung Shin; Lim, Youn Hee; Choi, Yoon Jung; Kim, Soontae; Bae, Hyun Joo; Han, Changwoo; Lee, Young Ah; Hong, Yun Chul (Environmental Research, 2020)
Background: Previous studies have suggested links between exposure to ambient air pollutants and increased risk of congenital heart defects. However, few studies have investigated the association between other congenital diseases and traffic-related air pollution. In this study, we assessed the relationship between prenatal exposure to fine particulate matter (PM2.5) and nitrogen dioxide (NO2) with congenital diseases in South Korea. Methods: Patients with one or more congenital diseases and a control group of patients with non-infective gastroenteritis and colitis with a case:control ratio of 1:3 were obtained from the National Health Insurance Service data for 2008–2013 in South Korea. We estimated the associations of PM2.5 and NO2 exposures with congenital diseases using generalized estimation equations after controlling for covariates. Results: Maternal PM2.5 exposure during the first and second trimester showed positive associations with overall congenital diseases, with changes of 14.7% (95% confidence intervals (CI), 9.3%, 20.3%) and 16.2% (95% CI, 11.0%, 21.7%), respectively, per 11.1 μg/m3 and 10.2 μg/m3 increase of PM2.5 interquartile range (IQR). Similarly, NO2 exposure during the first and second trimester was associated with increased numbers of overall congenital anomalies, with 8.2% (95% CI, 4.2%, 12.3%) and 15.6% (95% CI, 9.3%, 22.2%) more cases, respectively, per 10.6 ppb increase of NO2. We found that maternal PM2.5 exposure during the first and second trimesters of pregnancy was significantly associated with increased risk of specific congenital diseases, including subtypes affecting the circulatory, genitourinary, and musculoskeletal system. However, no significant associations were observed during the third trimester. Maternal NO2 exposure across the entire pregnancy was associated with malformations of the musculoskeletal system. Conclusions: Our study identified significant links between in utero exposure to PM2.5 and NO2 and certain congenital diseases, and suggests that stricter controls on PM2.5 and NO2 concentrations are required.
Keywords: Air Pollutants; Air Pollution; Environmental Exposure; Female; Humans; Maternal Exposure; Nitrogen Dioxide; Particulate Matter; Pregnancy; Prenatal Exposure Delayed Effects; Republic of Korea; Case-control study design; Congenital diseases; Fine particulate matter; Nitrogen dioxide; Pregnancy